2016
DOI: 10.1007/s00248-016-0838-1
|View full text |Cite
|
Sign up to set email alerts
|

Flowers and Wild Megachilid Bees Share Microbes

Abstract: Transmission pathways have fundamental influence on microbial symbiont persistence and evolution. For example, the core gut microbiome of honey bees is transmitted socially and via hive surfaces, but some non-core bacteria associated with honey bees are also found on flowers, and these bacteria may therefore be transmitted indirectly between bees via flowers. Here, we test whether multiple flower and wild megachilid bee species share microbes, which would suggest that flowers may act as hubs of microbial trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
163
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(189 citation statements)
references
References 57 publications
5
163
1
Order By: Relevance
“…In fact, it has been suggested that flowers act as bacterial hubs for bees (McFrederick et al . ). The less dramatic effect observed in our study could be explained by the structure of the tomato flower.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, it has been suggested that flowers act as bacterial hubs for bees (McFrederick et al . ). The less dramatic effect observed in our study could be explained by the structure of the tomato flower.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of other arthropod animals indicate that transmission pathways have fundamental influence on microbial symbiont persistence and evolution. For example, bees may acquire certain putative probiotics through maternal inheritance (vertical transmission) [52], while the core gut microbiome of honey bees is transmitted socially via hive surfaces [53], and the initial establishment of symbiotic gut bacteria in the turtle ant occurs after pupation via oral-rectal trophallaxis [54]. The shrimp usually care for the fertilized eggs, however the eggs are also exposed to environmental water with microbes, and the mechanism of selecting indigenous gut microbes might be the key to answer the inheritance of gut microbes in shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, solitary bee nests harbor highly diverse bacterial communities (Keller, Grimmer, & Steffan‐Dewenter, ; Lozo et al, ; McFrederick & Rehan, ; Mohr & Tebbe, ; Voulgari‐Kokota, Grimmer, Steffan‐Dewenter, & Keller, ). However, only few studies have dealt with their role in larval health (Keller et al, ; McFrederick, Vuong, & Rothman, ) or their acquisition routes (McFrederick et al, ; Voulgari‐Kokota, McFrederick, Steffan‐Dewenter, & Keller, ). Bees leading a solitary lifestyle with no direct contact between multiple generations are excluded from the benefits of a social structure, where individuals are in constant interaction with their nestmates, and their nest microbiota is more susceptible to environmentally introduced bacteria (Keller et al, ; McFrederick et al, ; Rothman, Andrikopoulos, Cox‐Foster, & McFrederick, ; Voulgari‐Kokota, Grimmer, et al, ; Voulgari‐Kokota, McFrederick, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, only few studies have dealt with their role in larval health (Keller et al, ; McFrederick, Vuong, & Rothman, ) or their acquisition routes (McFrederick et al, ; Voulgari‐Kokota, McFrederick, Steffan‐Dewenter, & Keller, ). Bees leading a solitary lifestyle with no direct contact between multiple generations are excluded from the benefits of a social structure, where individuals are in constant interaction with their nestmates, and their nest microbiota is more susceptible to environmentally introduced bacteria (Keller et al, ; McFrederick et al, ; Rothman, Andrikopoulos, Cox‐Foster, & McFrederick, ; Voulgari‐Kokota, Grimmer, et al, ; Voulgari‐Kokota, McFrederick, et al, ). As a result, the establishment of steady host–microbe interactions requires different mechanisms and could be the result of more complex processes, where beneficial microbial interactions are reinforced and negative interactions with pathogens are minimized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation